Management of gastric varices: a French national survey. Issue 5 (May 2016) - Weil, Delphine; Cervoni, Jean-Paul; Fares, Nadim; Rudler, Marika; Bureau, Christophe; Plessier, Aurélie; Dao, Thong; Pauwels, Arnaud; Thabut, Dominique; Castellani, Paul; Oberti, Frederic; Carbonell, Nicolas; et al.
Abstract : Background and aims: Bleeding from gastric varices is more severe than that from esophageal varices, but its management remains debated. We aimed to determine how French hepatogastroenterologists manage cirrhotic patients with gastric varices. Methods: Hepatogastroenterologists ( n =1163) working in general or university hospitals received a self-administered questionnaire. Results: Overall, 155 hepatogastroenterologists (13.3%) from 112 centers (33.3%; 39/40 university hospitals, 73/296 general hospitals) answered. Primary prophylaxis was used by 98.1% of hepatogastroenterologists as follows: β-blockers 96.1% (93.8 vs. 97.0%; university vs. general hospitals respectively; P =0.57), glue obliteration 16.9% (17.2 vs. 16.3%; P =0.88), and transjugular intrahepatic portosystemic shunt (TIPS) 8.0% (12.7 vs. 4.6%; P =0.12). To manage bleeding, university hospitals had greater local access to glue obliteration (95.4 vs. 68.2%; P <0.001) and TIPS (78.5 vs. 3.5%; P <0.001). Early TIPS was proposed by 53.6% (72.1 vs. 39.2%; P <0.001). Glue obliteration was performed under general anesthesia (86.1%) using Glubran (43.1%) or Histoacryl (52.9%), and lipiodol (78.8%) with varying degrees of dilution (1 : 10 to 3 : 4). The injected volume per varix varied widely (1–20 ml). Glue obliteration, band ligation, or both were used by, respectively, 64.2, 18.2, and 17.5% of practitioners. Almost all hepatogastroenterologists (98%) performed secondary prophylaxis: β-blockers 74.7% (75.0 vs. 74.4%, university vs. general hospitals; P =0.93), glue obliteration 66.0% (76.9 vs. 57.6%; P =0.013), and TIPS 30.0% (39.1 vs. 23.3%; P =0.037). Conclusion: The management of gastric varices in France is heterogeneous across centers. University hospitals have better access to techniques such as glue obliteration and TIPS. As bleeding from gastric varices has a poor outcome, guidelines should be established to standardize clinical practices and design further studies. Abstract : Supplemental Digital Content is available in the text.